Drone marino CK-14 - Test rilievo del Tevere con ecoscandaglio Multibeam - Poli, Giorgio (GEOmedia, 2023)
During the TECHONOLOGY for ALL in November 2022, the CK-14 marine drone showed off its capabilities in control and guidance in the rough waters of the Tevere (Rome), beaten by the wind and strong currents. Its capabilities were demonstrated also a few weeks later at the Porto Antico di Traiano (Rome), where bathymetric surveys were carried out. This small, silent and maneuverable marine drone allows the installation of a wide range of scientific instruments, making it a ductile as well as performing ASV.